Law and division of power in the Crimean Khanate (1532-1774) : with special reference to the reign of Murad Giray (1678-1683) - Królikowska-Jedlińska, Natalia (The Ottoman Empire and its Heritage, 2019)
The Crimean Khanate was often treated as a semi-nomadic, watered-down version of the Golden Horde, or yet another vassal state of the Ottoman Empire. This book revises these views by exploring the Khanate's political and legal systems, which combined well organized and well developed institutions, which were rooted in different traditions (Golden Horde, Islamic and Ottoman). Drawing on a wide range of sources, including the Crimean court registers from the reign of Murad Giray (1678-1683), the book examines the role of the khan, members of his council and other officials in the Crimean political and judicial systems as well as the practice of the Crimean sharia court during the reign of Murad Giray.